Acyl-Enzymes as Thrombolytic Agents in a Rabbit Model of Venous Thrombosis - Smith, R A G; Dupe, R J; English, P D; Green, J (Thrombosis and Haemostasis, 1982)
A derivative of human lys-plasmin in which the active site has been reversibly acylated (BRL 26920; p-anisoyl human lys-plasmin) has been examined as a fibrinolytic agent in a previously described rabbit model of venous thrombosis and shown to be significantly more active and less fibrinogenolytic than free plasmin. A p-anisoylated derivative of a streptokinase (SK)-activated plasmin preparation was significantly less fibrinogenolytic in vivo than the non-acylated enzyme. Acylation increased the fibrinolytic activity of preparations of SK-plasmin activator complexes. BRL 26921, the active site anisoylated derivative of the primary 2-chain SK-plasminogen complex was the most potent fibrinolytic agent studied. SK-Val442-plasminogen complexes, free or acylated, were biologically inactive in this model and confirm the essential nature of fibrin binding processes for effective thrombolysis in vivo.
Keywords: Thrombolysis; Plasmin; Acyl-plasmin; Streptokinase-plasmin; Acyl-streptokinase-plasmin(ogen) complexes